Screening for Adult Attention-Deficit/Hyperactivity Disorder in a Psychiatric Outpatient Population with Specific Focus on Sex Differences - Corbisiero, Salvatore; Hartmann-Schorro, Raffaela M.; Riecher-Rössler, Anita; Stieglitz, Rolf-Dieter (Frontiers in Psychiatry, 2017)
Background/Aims: Attention-deficit/hyperactivity disorder (ADHD) is often overlooked in adults; moreover, the problem seems to be even more critical in women. In the present, observational screening study, a clinical, particularly adult outpatient population was examined regarding frequency and severity of a likely ADHD, whereby sex differences were of particular interest. Methods: 224 participants, 146 men and 78 women, were included. Based on data recorded with the self-rating WHO screening instrument Adult ADHD Self-Report-Scale (ASRS-v1.1), it was examined how many participants were conspicuous for adult ADHD by exceeding a predefined cutoff value (COV ≥4 for ASRS-6 and ≥12 for ASRS-18). To examine frequency distributions, χ2-square tests were conducted. For the inferential statistical comparison of means, t tests for independent samples or Mann-Whitney U-tests were calculated. In cases where distribution requirements were violated, were conducted. Results: 34.4% of the sample was screened positive in the ASRS-v1.1 screener short version, ASRS-6, while 17.4% were conspicuous in the symptom checklist, ASRS-18. There were indeed more men screened positive, but the difference in the frequency between the sexes was not statistically significant, indicating a balanced sex ratio. Further, severity of ADHD core symptoms inattention and hyperactivity/impulsivity was examined by comparing ASRS-18 symptom subscale scores. In concordance with the hypothesis, men and women did not differ in severity of symptoms. Conclusion: Results indicate that women might be affected by ADHD in a comparable manner as men; this emphasizes the importance for the awareness of ADHD in both sexes in clinical practice.